Pengaruh Digital Accounting Systems terhadap Kualitas Keputusan Keuangan melalui Kualitas Informasi Akuntansi pada Perusahaan Modern - Willy Cahya Sundara; Budi Al Amin; Afriani Pravitasari; Rina Oktiyani (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to analyze the effect of Digital Accounting Systems on Financial Decision Quality through Accounting Information Quality in modern companies. This research employed a quantitative explanatory approach using a survey design. Primary data were collected from 100 employees working in finance, accounting, and financial administration departments through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The findings reveal that Digital Accounting Systems have a positive and significant effect on Accounting Information Quality, Accounting Information Quality has a positive and significant effect on Financial Decision Quality, and Digital Accounting Systems also directly improve Financial Decision Quality. The mediation test confirms that Accounting Information Quality partially mediates the relationship between Digital Accounting Systems and Financial Decision Quality. These results imply that companies should not only adopt digital accounting technology but also strengthen system integration, data validation, transaction standardization, and user competence to ensure that digital accounting systems produce accurate, timely, relevant, and useful information for effective financial decision-making.